2020
DOI: 10.3390/world1030018
|View full text |Cite
|
Sign up to set email alerts
|

An Institutional Pressure and Adaptive Capacity Framework for Green Bonds: Insights from India’s Emerging Green Bond Market

Abstract: Although climate finance tools like green bonds have been gaining popularity in academia, the research has been limited to examining the financial viability and performance of this market. We explore a different research avenue related to institutional dynamics that are driving this market at the country level and shaping its adaptive capacity to climate change. Our paper introduces a new conceptual framework by linking institutional isomorphism with adaptive capacity dimensions in the green bond market. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…Therefore, the empirical results suggest that even without the government’s implicit coercive policies (such as that of Mainland China), both investors might have an environmental preference and prefer financial announcements that are in line with global voluntary disclosure practices (as seen in the case of Hong Kong market). Another finding in line with literature is that both stock markets were now merging toward integration in terms of market reactions, and this further legitimized the green bond market becoming more mainstream in the traditional financial sector ( Saravade and Weber, 2020 ). In addition, our study also showed that Mainland China’s financial market reactions were also moving closer to the international trends related to sustainable finance.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Therefore, the empirical results suggest that even without the government’s implicit coercive policies (such as that of Mainland China), both investors might have an environmental preference and prefer financial announcements that are in line with global voluntary disclosure practices (as seen in the case of Hong Kong market). Another finding in line with literature is that both stock markets were now merging toward integration in terms of market reactions, and this further legitimized the green bond market becoming more mainstream in the traditional financial sector ( Saravade and Weber, 2020 ). In addition, our study also showed that Mainland China’s financial market reactions were also moving closer to the international trends related to sustainable finance.…”
Section: Discussionsupporting
confidence: 74%
“…Others have identified potential drawbacks such as pricing differentials ( Hachenberg and Schiereck, 2018 ; Zerbib, 2019 ; Guo and Zhou, 2021 ) or lower returns between green and conventional bonds ( Bachelet et al, 2019 ; Larcker and Watts, 2020 ). Other studies have addressed green bond markets as an opportunity for both investors engaging with green finance ( Chiesa and Barua, 2019 ; Saravade and Weber, 2020 ) and for countries that will face significant climate risks in the future ( Broadstock and Cheng, 2019 ; Chiesa and Barua, 2019 ; Fatica and Panzica, 2021 ). To support the transition to a low-carbon economy, major institutional actors such as investors and governments have started to issue green bond policies and green fiscal measures to reduce climate risk exposure ( Monasterolo and Raberto, 2018 ; Hunt and Weber, 2019 ; Saravade and Weber, 2020 ; Fatica et al, 2021 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Saravade and Weber (2020) investigated the institutional characteristics that drive India's green bond market using a mixed-method exploratory approach. The findings reveal that a variety of social actors, ranging from formal institutions like regulators and investors to informal ones like advocacy groups, are critical in determining the validity of the green bond market.…”
Section: Overview Of Green Bonds: a Literture Reviewmentioning
confidence: 99%